Problematika Dalam Penerapan Pembagian Warisan - Syahrando Muhti; Reky Yuliansyah; Trianda Lestari (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
There are 3 forms of inheritance systems in Indonesia, namely Islamic inheritance, customary inheritance and civil inheritance (BW). There are various different division systems and different sources. Islamic inheritance law is based on the Koran and the Prophet's Sunnah, customary inheritance law. based on customary/hereditary provisions, while civil inheritance is based on the provisions of civil law regulations part book II. However, in the division of inheritance there are still problems that occur, giving rise to conflicts and even inheritance disputes. This research uses legal theory, quoted from the opinion of expert Santoso Pudjosubroto, who believes that inheritance law is a law that regulates whether and how the rights and obligations regarding a person's property when he dies will be transferred to other people who are still alive. This research method uses a normative method by referring to regulations in the inheritance law distribution system, such as the Compilation of Islamic Law, customary law, and BW. So the title that can be drawn from this research is Problems in the Implementation of Inheritance Division.